An Introduction to the Problem of Hebraic Philosophical Style - Johnson, Dru (Philosophia Christi, 2024)
The philosophy origins story often begins in the sixth century, in Greece, and in the mind. Biblical Philosophy: A Hebraic Approach to the Old and New Testaments reassesses that story to justify new side-by-side comparisons between Hellenic and Hebraic philosophical styles. The Hebrew Bible represents a sophisticated philosophical method worthy of putting in league with the Aegean traditions that developed centuries later. In this analysis, the Hebrew philosophical style starts in Asia, in the Iron Age, and in the social body of Israel. As Christian philosophers, the touchpoint for the Christian philosophical tradition may require adjustment in light of the philosophical reasoning of the Hebrew Bible extending into the New Testament.